Studies on the mineral nutrition of the rice plant: XIV. effects of excess of Al, Cl and Mn on the varieties IAC-25 and IAC-47 - Malavolta, E.; Berto, P.N.A.; Katayama, P.S.; Santos, P.M.; Arevalo, R.A.; Rufino, R.L.; Naves, R.V.; Rodrigues, T.E.; Leite, J.S.T.; Stipp, S.R.C.; Daghlian, C.; Amaral, W.; et al. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1981)
Rice plants were grown either in full strength nº 2 solution of HOAGLAND & ARNON (1950) or in the same with high levels of Al, Cl and Mn (25, 1750 and 25 ppm, respectively). Plants with excess of each element did not complete the reproductive phase of development. Symptoms of toxicity appeared in response to the high levels supplied in the substrate. Dry matter production was relatively more affected in the case of the variety IAC-47. On the other hand, both varieties were more sensitive to Mn toxicity than to Al excess. The leaves had the following levels of the elements under the respective treatments, respectively for the variety IAC-25 and for the variety IAC-47; Al-107 and 221 ppm; Cl-87,500 and 17,500 (lower and upper leaves), 44,125 and 16,250 (lower and upper leaves); Mn - 1,670 and 1,769. The Al content of the roots was 5,639 and 5,872 ppm. Al toxicity decreased P content in all plant parts.